(untitled) (Biological Sciences - PJSIR, 2003)
The biological activities of the nitrogen containing conjugated heterocyclic compounds are considerably used phannaceuti cally as antiulcer, antimalarial, tubercluocidal and sedatives besides their uses as dyes in the tex1.ile industries, pesticides, stabilizers and inhibitors etc (Cheeseman 1963; Cheeseman and Werstuick 1978).